Risks of reproductive loss and placenta-mediated pregnancy complications in women with antiphospholipid antibodies - Yu. S. Dolgova; D. R. Eremeeva; M. S. Zainulina (Акушерство, гинекология и репродукция, 2021)
Introduction. Antiphospholipid syndrome (AРS) is a multisystem disease characterized by elevated levels of antiphospholipid antibodies (AРA), arterial and/or venous thrombosis, thrombocytopenia, and habitual miscarriage. Various AРA types have multifactorial and indirect effects on pregnancy course from the earliest stages, leading to termination of pregnancy and putting the prerequisites for further obstetric complications. Aim: determine rate and relative risk of pregnancy complications in AРA carriers. Materials and Methods. The retrospective study, conducted between 2017 and 2019, included 268 pregnant women. All women underwent a comprehensive study consisting of clinical examination and laboratory methods. AРA of IgM and IgG classes were measured by using ELISA, lupus anticoagulant (LA) was estimated by using a coagulometer. Results. APA were detected in 213 (79.48 %) women examined; 55 (20.52 %) patients (n = 55) lacked APA. Failed in vitro fertilization attempts were 2 times more common in women with AРA (10.33 vs. 5.45 %, respectively; p < 0.001). Also, significant differences were found in this group in antenatal fetal death (4.23 vs. 1.82 %, respectively; p < 0.001) and chronic placental insufficiency without fetal malnutrition (23.47 vs. 18.18 %, respectively; p < 0.05). Of 165 women with early pregnancy loss syndrome, AРA were found in 130 (78.79 %), late pregnancy loss – in 29 (76.32 %) and antenatal fetal death – in 9 (90.0 %) women carrying serum AРA. The relative risks of unfavorable pregnancy outcomes have been identified for various AРA subtypes. Conclusion. Identifying clear-cut relative risks of adverse pregnancy outcomes for various subtypes of antiphospholipid antibodies will allow to determine risk groups and develop a special treatment algorithm for preventing pregnancy complications and perinatal losses.